2016
DOI: 10.1016/s0140-6736(16)30584-0
|View full text |Cite|
|
Sign up to set email alerts
|

Haemorrhoidal artery ligation versus rubber band ligation for the management of symptomatic second-degree and third-degree haemorrhoids (HubBLe): a multicentre, open-label, randomised controlled trial

Abstract: SummaryBackgroundOptimum surgical intervention for low-grade haemorrhoids is unknown. Haemorrhoidal artery ligation (HAL) has been proposed as an efficacious, safe therapy while rubber band ligation (RBL) is a commonly used outpatient treatment. We compared recurrence after HAL versus RBL in patients with grade II–III haemorrhoids.MethodsThis multicentre, open-label, parallel group, randomised controlled trial included patients from 17 acute UK NHS trusts. We screened patients aged 18 years or older presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 27 publications
1
131
2
2
Order By: Relevance
“…The findings from the study, along with those from HubBLe and LingaLongo, 16,72 have added greatly to our understanding of the management of haemorrhoids. This study showed better overall generic quality of life over the 24-month follow-up period for TH over SH.…”
Section: Summary Of Findingsmentioning
confidence: 86%
See 3 more Smart Citations
“…The findings from the study, along with those from HubBLe and LingaLongo, 16,72 have added greatly to our understanding of the management of haemorrhoids. This study showed better overall generic quality of life over the 24-month follow-up period for TH over SH.…”
Section: Summary Of Findingsmentioning
confidence: 86%
“…The trend over a longer period, however, suggested that the greater failure rate for RBL may eventually reach a level that justified the increased cost of SH. More robust data on the outcome of RBL have since come from the HubBLe (haemorrhoidal artery ligation versus rubber band ligation for the management of symptomatic second-degree and third-degree haemorrhoids) study 16 comparing HAL with RBL, which shows that RBL, when given as a course of two or three treatments, is as clinically effective as HAL.…”
Section: Evidence Leading To the Inception Of The Ethos Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The database used by the Sheffield CTRU was developed in-house and is a web-based system that allows remote data entry which can be adapted to allow participants to enter their data directly. To date, the unit has also used the system for this purpose on one randomised trial comparing two procedures for the treatment for haemorrhoids [14] and one observational study of pregnant females with suspected pulmonary embolism [15]. In both cases, participants were asked whether they could be contacted electronically, by post, or either.…”
Section: The Research In Context: Other Experiences Of Electronic Andmentioning
confidence: 99%